Modifying of the Eutectic Silumin surface by the Electron-Ion-Plasma Method; Perspective Plasma Technologies - Ivanov Yu. F. Yuriy Fedorovich; Petrikova E. A. Elizaveta Alekseevna; Lopatin I. V.; Tolkachev O. S. Oleg Sergeevich; Rygina M. E. Mariya Evgenjevna (2019, 2019)
Title screen